Epidemiology of pediatric femur fractures in children: the Swedish Fracture Register - Engström, Zandra (BMC Musculoskelet Disord, 2020)
BACKGROUND: Although femur fractures in children are rare, they are the most common fractures in need of hospitalization. We sought to describe the epidemiology and treatment of pediatric femur fractures recorded in the Swedish Fracture Register (SFR). We also studied the relationship between femur fractures, age, sex, fracture pattern, injury mechanism, seasonal variation and treatment. METHODS: This nationwide observational register study was based on the pediatric part of the SFR. We included all patients < 16 years of age who were registered in the SFR from 2015 to 2018. RESULTS: Of the 709 femur fractures, 454 (64%) occurred in boys. Sixty-two of these fractures were proximal (9%), 453 shaft (64%) and 194 distal (27%). A bimodal age distribution peak was observed in boys aged 2–3 and 16–19 years. In contrast, the age distribution among girls was evenly distributed. Younger children were mainly injured by a fall, whereas older children sustained their fracture because of traffic accidents. Non-surgical treatment prevailed among younger children; however, prevalence of surgical treatment increased with age. CONCLUSIONS: We found a lower ratio between boys and girls (1.8:1) compared to earlier studies. The bimodal age distribution was seen only in boys. Falls were the most common injury in younger children, whereas traffic-related accidents were the most common in adolescents. With age, there was a corresponding increase in surgical treatment.